A Phase I study evaluating the effect of age and weight on the pharmacokinetics of an injectable formulation of diclofenac solubilized with hydroxypropyl-β-cyclodextrin - Goldwater R (Dove Medical Press, 2016)
Ronald Goldwater,1 William G Kramer,2 Douglas A Hamilton,3,4 Eric Lang,4,5 Jianyuan Wang,4 Donna E Madden,4 Peter G Lacouture,6,7 Atulkumar Ramaiya,8 Daniel B Carr4,9 1PAREXEL International, Baltimore, MD, 2Kramer Consulting, LLC, North Potomac, MD, 3New Biology Ventures, LLC, San Mateo, CA, 4Javelin Pharmaceuticals, Cambridge, MA (now Hospira, a Pfizer company, Lake Forest, IL, USA), 5Covance, Princeton, NJ, 6Magidom Discovery, LLC, Lindenhurst, IL, 7Brown University School of Medicine, Providence, RI, 8Global Medical Affairs, Hospira, a Pfizer company, Lake Forest, IL, 9Department of Anesthesiology, Tufts Medical Center, Boston, MA, USA Purpose: The analgesic and opioid-sparing effects of nonsteroidal anti-inflammatory drugs can be beneficial in postoperative populations. Hydroxypropyl-β-cyclodextrin (HPβCD)-diclofenac is an injectable formulation of diclofenac solubilized with HPβCD that is administered as a low-volume intravenous bolus. This open-label, single-dose study examined the effects of age and weight on the pharmacokinetic (PK) profile of HPβCD-diclofenac. Methods: Eighty-eight adult volunteers were enrolled. An age-based cohort included 34 subjects 55–82 years old stratified into three groups and receiving HPβCD-diclofenac 18.75 mg. A weight-based cohort included 54 subjects stratified into five groups based on body weight and body mass index and receiving HPβCD-diclofenac 37.5 mg. PK analysis was performed on blood samples collected predosing and at predefined intervals (5, 10, 20, 30, and 45 minutes; 1, 1.5, 2, 2.5, 3, 4, 6, 8, 10, 12, and 18 hours) postdosing. Diclofenac PK parameters were examined in the individual cohorts, and regression analyses of the relationship between age, weight, and PK parameters were performed on pooled data from all enrolled subjects. Results: Examination of the age-based cohort revealed similar diclofenac PK parameters across age groups. PK parameters were likewise similar across weight groups in the weight-based cohort. Regression analysis on pooled data from the age- and weight-based cohorts revealed that increasing body weight was associated with a significant increase in diclofenac clearance (CL), suggesting decreased exposure in high-weight patients. Analysis of the pooled population also demonstrated an inverse relationship between age and elimination half-life (t1/2), likely due to a decrease in the volume of distribution (Vz) with increased age, not a change in CL. There were no deaths, serious adverse events, or adverse events that led to discontinuation. Conclusion: This study suggests that the CL of diclofenac is not dependent on age in elderly subjects receiving HPβCD-diclofenac but indicates that diclofenac CL increases with increasing body weight. Keywords: analgesia, pain control, pharmacokinetics, obesity, elderly, NSAID